You Pretend, I Laugh: Associations Between Dyadic Pretend Play and Children's Display of Positive Emotions - Rao, Zhen; Gibson, Jenny L. (Frontiers in Psychology, 2021)
Background: Understanding how pretend play is related to positive emotions is important for supporting children’s development and promoting their wellbeing. However, previous studies have mainly examined this association at individual levels and overlooked the potential links at interpersonal levels. This is an important knowledge gap because pretend play is commonly performed in social contexts. The current study investigates how peer pretend play is associated with children’s display of positive emotions at both individual and dyadic levels. Methods: 108 Chinese children (Mage = 8.95 years, SD = 0.99, 51.9% girls) were observed playing in peer dyads with toys. An interaction of 10 minutes was coded for each child’s pretend play behavior, social and emotional pretend play themes, and display of positive. Multilevel modelling was used to examine age and gender differences in peer pretend play. Actor-Partner Interdependence Models were estimated to test the hypothesized associations between dyadic pretend play and children’ display of positive emotions. Results: Compared to children whose playmates engaged in less pretend play, children whose playmates engaged in more pretend play were more likely to display positive emotions (β = 0.33, p = .021). Additionally, children’s display of positive emotions was predicted by both their own (β = 0.64, p =.027) and their playmate’s (β = 0.93, p =.01) pretend play with emotional themes. Compared to younger children, older children were less likely to engage in pretend play (β = -3.9, p = .002), but more likely to engage in pretend play with social themes (β = 1.1, p = .03) when the total frequency of pretend play was controlled for. Boys were 4.9 times and 2.16 times as likely as girls to create aggressive pretend themes (p <.001) and non-aggressive negative pretend themes (p =.007) respectively. No significant gender differences were found in positive pretend themes. Conclusions: Pretending with peers may increase not only children’s own, but also their play partner’s display of positive emotions. Pretend play may not simply decline in middle childhood as previously assumed.